THE INFLUENCE OF CUSTOMER SERVICE, CUSTOMER EXPERIENCE AND BRAND TRUST ON MSI CONSUMER SATISFACTION (Case Study On Silver Ion MSI Customers In Tiban Housing Stocking Batam City) - Rimayang Anggun Ramli; Trisna Kurnia (Universitas Riau Kepulauan, 2019)
This research aims to examine and analyze the influence of customer service, customer experienceand brand trustto customer satisfaction of MSI Silver Ion in Tiban Housingstocking Batam City. Data collected through questionnaires and conducted using SPSS version 20. The sampling technique used is the census methods and techniques testing techniques data used in this study include factor analysis, validity test, reliability test with AlphaCronbach. Classical assumption test and multiple linear regression analysis, to test and prove the hypothesis of the study Hypothesis testing using t test showed that the variables of customer service does notsignificantlyinfluence the customer satisfaction, the customer experience does not significantlyinfluence customer satisfaction, brand trust significantly influence to customer satisfaction. Then through the F test can be found that the three independent variables simultaneously have a significant effect on customer satisfaction. Adjusted R² number of 0.462 show that 46.2% of consumer satisfaction variables can be explained by the three independent variables in the regression equation, while the remaining 50.6% is explained by other variables outside the variables used in the study.